Routine first‐trimester combined screening for pre‐eclampsia: pregnancy‐associated plasma protein‐A or placental growth factor?. (13th September 2021) - Noël, L.; Guy, G. P.; Jones, S.; Forenc, K.; Buck, E.; Papageorghiou, A. T.; Thilaganathan, B.
ABSTRACT: Objective: To compare the screening performance of serum pregnancy‐associated plasma protein‐A (PAPP‐A) vs placental growth factor (PlGF) in routine first‐trimester combined screening for pre‐eclampsia (PE), small‐for‐gestational age (SGA) at birth and trisomy 21. Methods: This was a retrospective study nested in pregnancy cohorts undergoing first‐trimester combined screening for PE and trisomy 21 using The Fetal Medicine Foundation (FMF) algorithm based on maternal characteristics, nuchal translucency thickness, PAPP‐A, free beta‐human chorionic gonadotropin, blood pressure and uterine artery Doppler. Women at high risk for preterm PE (≥ 1 in 50) received 150 mg of aspirin per day, underwent serial fetal growth scans at 28 and 36 weeks and were offered elective birth from 40 weeks of gestation. PlGF was quantified retrospectively from stored surplus first‐trimester serum samples. The performance of combined first‐trimester screening for PE and SGA using maternal history, blood pressure, uterine artery pulsatility index and either PAPP‐A or PlGF was calculated. Similarly, the performance of combined first‐trimester screening for trisomy 21 was calculated using either PAPP‐A or PlGF in addition to maternal age, nuchal translucency thickness and free beta‐human chorionic gonadotropin. Results: Maternal serum PAPP‐A was assayed in 1094 women, including 82 with PE, 111 with SGA (birth weight < 10 th centile), 53 with both PE and SGA and 94 with fetal trisomy 21. PlGF levels were obtained retrospectively from 1066/1094 women. Median serum PlGF multiples of the median was significantly lower in pregnancies with PE (1.0 (interquartile range (IQR), 0.8–1.4); P  < 0.01), SGA (1.0 (IQR, 0.8–1.3); P  < 0.001) and trisomy 21 (0.6 (IQR, 0.5–0.9); P  < 0.0001) compared to in controls (1.2 (IQR, 0.9–1.5)). There was no significant difference in the performance of first‐trimester screening using PAPP‐A vs PlGF for either preterm PE (area under the receiver‐operating‐characteristics curve (AUC), 0.78 vs 0.79; P =  0.55) or term PE (AUC, 0.74 vs 0.74; P  = 0.60). These findings persisted even after correction for the effect of targeted aspirin use on the prevalence of PE. Similarly, there were no significant differences in sensitivity and specificity of combined screening for SGA or trisomy 21 when using PAPP‐A vs PlGF. Conclusions: Using either PlGF or PAPP‐A in routine first‐trimester combined screening based on maternal characteristics, blood pressure and uterine artery Doppler does not make a significant clinical difference to the detection of PE or SGA. Depending on the setting, biomarkers should be chosen to achieve a good compromise between performance and measurement requirements. This pragmatic clinical‐effectiveness study suggests that combined screening for PE can be implemented successfully in a public healthcare setting without changing current protocols for the assessment of PAPP‐A in the first trimester. © 2021 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology. Abstract : Linked article: There is a comment on this article by Cuckle. Click here to view the Correspondence.